JSTR 2019
DOI: 10.7176/jstr/5-5-9
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Edible Aquatic Insects for Feed Rations of Poultry Animals

Abstract: With the rapidly increasing population of people today, mass production, inexpensive labor, low cost, high market share and economic sufficiency are the first issues that come to mind in poultry farming. The most important cost in the poultry farming sector is production of food. As insects are in the richest group that provides species variations in the feeds for living beings, they are a significant source of feeding poultry animals. In addition to this, it is believed that aquatic insects (Coleoptera) are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It is a valuable and innovative proposal to use edible aquatic insects as feed, and some species, such as mosquito larvae, could provide a convenient source of feed [ 19 , 165 ]. Mosquitos have the distinct biological characteristics of a short lifecycle, high occurrence densities, and wide distribution.…”
Section: Discussionmentioning
confidence: 99%
“…It is a valuable and innovative proposal to use edible aquatic insects as feed, and some species, such as mosquito larvae, could provide a convenient source of feed [ 19 , 165 ]. Mosquitos have the distinct biological characteristics of a short lifecycle, high occurrence densities, and wide distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Shaw and Mark (1980) reported that on a 13.5 ha farm in Hong Kong, chicken manure was successfully used to rear chironomids which were then used to feed fishes -the larval yield being 25 g/m 2 per week. The intervening 40 years do not appear to have produced further examples, although (Bektas and Guler, 2019) have reported the addition of aquatic insects to the feed rations of poultry.…”
Section: Dipteramentioning
confidence: 99%